2019
DOI: 10.1101/2019.12.26.889071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benzaldehyde Synthases Are Encoded by Cinnamoyl-CoA Reductase Genes in Cucumber (Cucumis sativusL.)

Abstract: Benzaldedyde, commonly detected in plant VOC (volatile organic compounds) profiling, is derived from phenylalanine. However, the last enzymatic step for benzaldedyde formation, designated as benzaldehyde synthase, remains elusive for long time. Here, we demonstrated that cinnamoyl-CoA reductases are responsible for benzaldedyde production in cucumber (Cucumis sativus L.). Comprehensive tissue specificity of VOC profiling revealed that benzaldehyde was specifically accumulated in root and flower of cucumber pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, under the action of numerous microorganisms and complex enzyme systems in Aspergillus oryzae koji, the nutrients in raw fish were decomposed and converted into a wide variety of metabolites, and the volatile esters were often more diverse. Liu et al used GC–MS to compare the volatile components of traditional fish sauce and koji fermented fish sauce, and found that the content of ester compounds in the koji fermentation fish sauce was significantly higher than the commercial fish sauce ( 27 ). Therefore, the ester flavor of fish sauce produced by koji fermentation was generally superior to heat preservation and enzyme adding process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, under the action of numerous microorganisms and complex enzyme systems in Aspergillus oryzae koji, the nutrients in raw fish were decomposed and converted into a wide variety of metabolites, and the volatile esters were often more diverse. Liu et al used GC–MS to compare the volatile components of traditional fish sauce and koji fermented fish sauce, and found that the content of ester compounds in the koji fermentation fish sauce was significantly higher than the commercial fish sauce ( 27 ). Therefore, the ester flavor of fish sauce produced by koji fermentation was generally superior to heat preservation and enzyme adding process.…”
Section: Resultsmentioning
confidence: 99%
“…Benzaldehyde could also be generated from Phe as a precursor. Briefly, Phe was transferred into cinnamic acid through Phe ammonia-lyase, followed by generating benzaldehyde under the action of benzaldehyde synthase ( 27 ). Nevertheless, this was only a theoretical method and required to be verified experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…High correlations (mean r = 0.42) were detected between expression of FxaC_21g33200 and abundances of: acetic acid, butyl ester; acetic acid, hexyl ester; acetic acid, octyl ester; hexanoic acid, octyl ester; and hexanoic acid, decyl ester. This highly expressed CCR in fruit potentially could catalyze substrates including precursor CoAs of medium‐chain esters, because a homolog of CCR was validated to convert benzoyl‐CoA to benzaldehyde (Liu et al ., 2019 ). A putative anthranilate phosphoribosyltransferase (FxaC_19g06300) catalyzing the reaction of free anthranilate to N‐(5‐phospho‐ d ‐ribosyl)‐anthranilate was associated with the Chr 5C methyl anthranilate (MA) GWAS peak.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it is known that benzaldehyde, commonly detected in plant VOC profiling, plays a key role in plant fitness. In plants, benzaldehyde biosynthesis is a product from trans-cinnamic acid, which is produced by the breakdown of phenylalanine [ 27 ]. Benzaldehyde and benzyl alcohol (probably derived from benalzaldehyde by an oxidoreductase) are found to be accumulated in cucumber roots and flowers [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In plants, benzaldehyde biosynthesis is a product from trans-cinnamic acid, which is produced by the breakdown of phenylalanine [ 27 ]. Benzaldehyde and benzyl alcohol (probably derived from benalzaldehyde by an oxidoreductase) are found to be accumulated in cucumber roots and flowers [ 27 ]. The VOCs describing CI leaves were in common with LS leaves, notably benzeneacetaldehyde and 3-hexen-1-ol, (Z)-, but the CI leaves were characterized by a higher number of VOCs, including also butanal, 3-methyl-, 2-hexenal and 2,4-hexadienal, (E, E)-.…”
Section: Resultsmentioning
confidence: 99%